The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19116714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Maxillary Oral Appliance Designs on Respiratory Variables during Sleep

Abstract: This study aimed to analyze the efficacy of maxillary oral appliance (MOA) designs on respiratory variables during sleep. At baseline, 23 participants underwent a sleep test with a portable device for two nights and were categorized as participants with mild obstructive sleep apnea (mild-OSA) (n = 13) and without OSA (w/o-OSA) (n = 10). Three types of MOAs, standard-OA (S-OA), palatal covering-OA (PC-OA), and vertically increasing-OA (VI-OA), were each worn for three nights, and sleep tests with each MOA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…No significant differences in treatment efficacy were reported by the authors, but the patients’ compliance was higher for the device with the smaller interincisal opening. By contrast, Ye Min Soe et al [ 24 ] suggested that the increased vertical distance between the maxilla and mandible, due to the appliance, affected the exacerbation of the respiratory status during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences in treatment efficacy were reported by the authors, but the patients’ compliance was higher for the device with the smaller interincisal opening. By contrast, Ye Min Soe et al [ 24 ] suggested that the increased vertical distance between the maxilla and mandible, due to the appliance, affected the exacerbation of the respiratory status during sleep.…”
Section: Discussionmentioning
confidence: 99%